Business of Uncertainties: An Afflict of COVID-19 on Indian Insurance - Arora, Anjali; Arora, Geeta (Journal of Graphic Era University, 2021)
COVID-19 had far-reaching consequences for different economic sectors around the world. While the impact was not standardised throughout, one thing was consistent: every sector and region, including India and the Indian insurance sector, faced challenges in adapting to the new normal. The insurance industry provided both life and non-life or general insurance. COVID-19 had a mixed effect on the insurance industry. The effect of COVID-19 on the insurance industry was not uniform; some products saw a significant increase in business, while others saw a significant decrease. The aim of this research is to examine and assess the overall effect of COVID-19 on the insurance industry with emphasis on the steps to be taken to prepare the insurance sector to deal with these types of the consequences in the future. Data from the regulatory authority’s website is used to compile and analyse the findings of the study.